Research on the Application of Acoustic Simulation Based on iNoise in the Evaluation of Factory Boundary Noise. Issue 1 (1st April 2022) - Wan, Yupeng; Zhou, Yuanbo; Yu, Mingli; Yi, Gaojun
Abstract: The acoustic simulation platform iNoise is a simulation software released by Dutch DGMR company for industrial noise in recent years. So far, the research on the applicability verification of this simulation platform and the related research of this platform to guide the specific engineering quality have not been found in China. Taking the noise control project of a natural gas purification plant as an example, this paper makes a three-dimensional modeling and simulation analysis of the boundary noise of the plant by using the new platform. The applicability of the new acoustic simulation software has been preliminarily verified from the acceptance test results of this application case. In this project, the platform can realize the basic functions of the traditional noise simulation software. The platform can normally carry out noise reduction design and noise prediction and achieve ideal results.